Comparative Sero-prevalence of Herpes Simplex Virus Type-1 IgG Antibodies in Nigerian Children by Two Methods; IFA and ELISA - Shaibu A. M.; Aminu M; Musa B. O. P.; Bugaje M. A. (UMYU Journal of Microbiology Research)
Herpes simplex virus type-1 (HSV-1) are common cause of fatal sporadic encephalitis in 70% of children and can cause chronic ulcerative infection in immuno- suppressed children leading to latency with subsequent reactivate in the conjunctiva resulting in scarring, thickening of the cornea and blindness. This comparative study determined the sero-prevalence of HSV-1 IgG antibodies in children attending some selected Hospitals in Kaduna state, Nigeria. A total of 377 blood samples were collected from children less than five years old attending some selected hospitals in Kaduna State and analyzed for HSV-1 IgG antibodies employing Enzyme immune assay technique by using commercially available ELISA Kits and Indirect Fluorescent Antibody (IFA) test. Sero-prevalence rate of 57.8 % (218 /377) was obtained by ELISA and 67.4% (255/377) by IFA test.  The highest prevalence of HSV-1 infection was obtained in children in age group 49-60 months (85.2%) and lowest in children in age group 13-24 months (44.8%). Herpes simplex virus type -1 infection was significantly associated with age. Though a higher prevalence was obtained in female children than male children the difference observed in the prevalence was not statistically significant .The infection was significantly associated with children who were in school (χ2= 15.28, df = 1, P= 0.001) by only the ELISA test. Clinical symptoms significantly associated with HSV-1infection in children in this study were febrile illnesses, conjunctivitis, jaundice, skin infections and oro-facial lesions while the risk factors were age and educational status of children. Over half of the children sampled were protected from HSV-1 infection while about 40% of the children were susceptible to the infection and were at risk of developing severe HSV-1 manifestation which includes keratitis, encephalitis and Keratoconjunctivitis.